Stress Testing Corporate Balance Sheets in Emerging Economies - Chow, Julian (Washington, D.C. : International Monetary Fund, 2015)
In recent years, firms in emerging market countries have increased borrowing, particularly in foreign currency, owing to easy access to global capital markets, prolonged low interest rates and good investment opportunities. This paper discusses the trends in emerging market corporate debt and leverage, and illustrates how those firms are vulnerable to interest rate, exchange rate and earnings shocks. The results of a stress test show that while corporate sector risk remains moderate in most emerging economies, a combination of macroeconomic and financial shocks could significantly erode firms' ability to service debt and lead to higher debt at risk, especially in countries with high shares of foreign currency debt and low natural hedges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet